UNSUR KEJENAKAAN DALAM NOVEL TETRALOGI LASKAR PELANGI KARYA ANDREA HIRATA ANALISIS STRUKTURAL - ANA MUSTAFIDAH (Program Studi Pendidikan Bahasa Indonesia STKIP-PGRI Bangkalan, 2020)
Jokes in novels give certain appeal to the reader. The jokes in the Laskar Pelangi Tetralogy novel by Andrea Hirata Structural Analysis focuses on the characters and plot in the novel. This novel is analyzed using the structural approach. Through structural analysis, the bond between one element and another can be clearly seen because it can analyze these elements completely and integrated. The purpose of this research is to describe the characters’ jokes and plots in the Laskar Pelangi Tetralogy novel by Andrea Hirata. This research was examined using qualitative research methods. The data collection method was in the form of documentation method. The data collection technique uses the technique of reading, listening, and note-taking. Data analysis method uses descriptive method. The data analysis technique of this study was to analyze the contents of the Laskar Pelangi Tetralogy novel by Andrea Hirata. Referring to the results of this study, there are jokes in the Laskar Pelangi Tetralogy novel by Andrea Hirata, namely a character who has a witty characteristic presented through direct description, character names, actions of characters, and character dialogue. The plot in the novel is presented through the principle of plotting, which is the surprise in the novel. The author presents the plot in this novel gradually to achieve a surprise that really makes the reader get a surprise at the flow part. The jokes in this novel predominantly include parikena jokes, satire, cynicism, play, and salapstick. Keywords: Jokes, plot, structural, character.